PERBEDAAN PERSEPSI ANTAR KELOMPOK PROFESI TERHADAP KEBIJAKSANAAN KORPORASI DALAM PENCAPAIAN VISI DAN MISI ORGANISASI - Mashur Razak (AkMen JURNAL ILMIAH, 2011)
This study aims to analyze whether there are differences in perception among certain occupational groups to the wisdom koporasi in achieving the vision and mission of the organization. The sample in this study are a group of professionals in the field of education and occupational groups in banking. The method used is descriptive qualitative and quantitative methods. Analysis tool used is the statistical analysis tool that is an average of different test saples via independent t-test is to determine the degree of difference on the variables measured in samples that are independent in this study. The results of this study prove that there was no significant difference between perceptions closely and professional groups in education with professional groups in the field of Banking in the six indicators of research that is the attitude, motivation, interests, experiences, social environment and self-concept. This study proves that there is a close and significant differences between the perceptions of professional groups in education with professional groups in the field of Banking in the four indicators namely research expectations, working conditions, needs and the suitability of time.